2008
DOI: 10.1007/s11434-008-0054-6
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation/photoionization processes of chlorobromomethane induced by femtosecond laser pulses with pump-probe scheme

Abstract: The photodissociation/photoionization processes of chlorobromomethane (CH 2 BrCl) induced by femtosecond laser pulses have been investigated using pump-probe scheme combined with the time-of-flight mass spectra. The dominate photoproducts are observed at different delay time of the pump (400 nm) and probe (800 nm) pulses and the corresponding time-dependence of them is obtained. The results show that the decaying time of the molecule CH 2 BrCl in the A-band is in the 100 fs. The decaying tendencies of the frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The latter feature has been previously reported in TOF spectra of CH 2 BrCl, CH 2 ICl, CH 2 IBr, and CH 2 I 2 obtained from interaction with 800 nm TL pulses. 20,21,31,32,46 The only exception is CH 2 FCl, where the M + yield is greater than that of the fragment CH 2 F + . This property arises because the appearance energy for CH 2 F + lies much higher above the IE of CH 2 FCl as compared to other molecules (cf.…”
Section: Reactivity Trends For All Eleven Halomethanesmentioning
confidence: 96%
See 1 more Smart Citation
“…The latter feature has been previously reported in TOF spectra of CH 2 BrCl, CH 2 ICl, CH 2 IBr, and CH 2 I 2 obtained from interaction with 800 nm TL pulses. 20,21,31,32,46 The only exception is CH 2 FCl, where the M + yield is greater than that of the fragment CH 2 F + . This property arises because the appearance energy for CH 2 F + lies much higher above the IE of CH 2 FCl as compared to other molecules (cf.…”
Section: Reactivity Trends For All Eleven Halomethanesmentioning
confidence: 96%
“…The central question considered in this work is whether systematic variation in observable yields analogous to Figure b occurs when the chemical reagents are replaced by photonic reagents. Ultrafast laser-induced dissociative ionization reactions using a set of photonic reagents with a fixed substrate or vice versa have been explored for many classes of molecules. These studies revealed detailed information about the physical mechanisms underlying the dissociation dynamics in individual molecules and/or identified specific photonic reagents that produce a desired yield of some observable, typically a particular photoproduct or ratio of photoproducts. In contrast, less attention has been given to examining families of chemically homologous molecules interacting with families of photonic reagents; previous investigations typically have examined only a few related molecules or a large set of unrelated molecules .…”
Section: Introductionmentioning
confidence: 99%